Perception vs Reality: Methicillin-Resistant Staphylococcus aureus Carriage Among Healthcare Workers at a Veterans Affairs Medical Center. (3rd November 2015) - Colburn, Nora E.; Cadnum, Jennifer; Flannery, Elizabeth; Chang, Shelley; Donskey, Curtis J.; Stiefel, Usha
Abstract : In a prevalence study of 209 healthcare workers, 18 (8.6%) and 13 (6.2%) carried methicillin-resistant Staphylococcus aureus in their nares or on their hands, respectively. However, 100 (62%) of 162 workers completing an associated survey believed themselves to be colonized, revealing a knowledge deficit about methicillin-resistant Staphylococcus aureus epidemiology. Infect. Control Hosp. Epidemiol. 2015;37(1):110–112